(untitled) (Marketing Journal, 2025)
This article discusses one of the important areas of development of the banking sector in modern conditions –the foreign experience of the system of remote customer service for banks is considered. A set of specific services was also analyzed, with the help of which bank customers can carry out various banking operations remotely, and remote banking services in the United States, European countries, and Russia, which are leaders in this direction, were studied.